Weanling Rabbit Mortalities Caused by Enteropathogenic Bacteria: Bacteriological and Pathological Investigation - Fatma M. Mohamed (Egyptian Society for Animal Management, 2019)
Samples of internal organs (liver, heart, spleen, kidney and intestinal contents) were aseptically collected from 120 freshly died newly weanling rabbits and subjected to isolation and identification of the causative bacterial pathogens. The causative pathogens were isolated and identified biochemically. E.coli and Salmonella (the major associated pathogens) were typed serologically and tested for antimicrobial agents. The bacterial infection prevalence rate was Escherichia coli (56.6%), Salmonella spp. (27.5%), Enterobacter spp. (7.5%), Citrobacter spp. (5%) and Proteus spp. (3.3%). Out of the 68 infections with E.coli, 30 were serotyped as O125 (ten), O127 (six), O128 (five), O86 (five) and untyped (four). Out of the 33 Salmonella infections, seven were serotyped as serovar S. goldcoast (four) and serovars S. magherafelt (three). E.coli serogroups were resistant to the majority of used antimicrobial and were sensitive only to Sulphamethazole. Both Salmonella serovars were sensitive to most antimicrobial used in this study but they were resistant to amoxicillin. Both infected rabbit groups with E.coli and Salmonella demonstrated obvious histopathological alterations in the intestine, liver and spleen. Both E.coli (O86) and Salmonella goldcoast were used for experimental infection of weanling rabbits (6-8 weeks). Five days post-infection and after observation of the clinical symptoms, animals were sacrificed and tissue samples from the intestine, liver, kidney and spleen were examined histopathologically. Utmost care must be taken around the time of weaning in rabbits.